PENGARUH PERSEPSI HARGA, LOKASI DAN CITRA TOKO TERHADAP KEPUTUSAN PEMBELIAN DAN DAMPAKNYA PADA MINAT BELI ULANG (Studi pada konsumen SMS Shop Matahari Lantai 1 Semarang) - Mualimah, 14.05.51.0024; Maskur, Ali (Students' Journal of Economic and Management, 2018)
This study aims to analyze the influence of each variable of Price Perception, Location And Image Store Against Purchase Decision And Its Impact On Buying Interest (Study on consumer SMS Shop Branch Matahari 1 Semarang). The population in this study is the consumer SMS Shop Branch Matahari 1 Semarang. The sample is determined by using purposive sampling with criteria: those who have already decided to buy milk at SMS Shop Matahari 1 and the minimum age of 16 years. Data analysis method used is through descriptive statistics, instrument test, model test and hypothesis test. The test instrument is tested with validity test and reliability test. Test model used is Test F (Goodness of Fit) and test Adj R2 (coefficient of determination). Furthermore, the hypothesis test in this study using regression analysis with t test with standard beta coefficient and significance level <0.05. Based on the results of hypothesis test concluded: 1. Price perceptions have positive and significant impact on purchasing decisions. 2. Location has positive and significant impact on purchasing decision. 3. Store Image has positive and significant impact on purchasing decision. 4. Purchase decisions have a positive and significant impact on repurchase interest Keywords: price perception, location, store image, purchase decision, buying interest.